Effect of Titania (TiO2) Addition to Zirconia Toughened Alumina (ZTA) Phases, Hardness and Microstructure - Manshor, Hanisah; Md Aris, Suriyana; Ahmad Azhar, Ahmad Zahirani; Abdullah, Ezzat Chan; Ahmad, Zainal Arifin (Trans Tech Publications, Switzerland, 2015)
Ceramic composites consist of zirconia toughened alumina (ZTA) with TiO2 as additive was fabricated via solid state sintering route. Numerous studies have indicated that TiO2 can be used as sintering additives for Al2O3 and the ability of microstructural control introduce by TIO2. The Vickers hardness of the obtained ZTA-TiO2 was evaluated as a function of different TiO2 addition. Each sample was dry mixed, uniaxially pressed and sintered at 1600 oC for 4 hours in pressureless condition. It is noticed that the presence of TiO2 greatly influenced the microstructure of Al2O3. Al2O3 grains tend to increase in size with the addition of more than 3 wt% TiO2. Characteristics of Vickers hardness increased from 1516.13 HV (0 wt% TiO2) to 1615.8 HV (3 wt% TiO2) due to the increased in bulk density from 3.90 g/cm3 (0 wt% TiO2) to 4.10 g/cm3 (3 wt% TiO2).